Tracing the Evolution of Blockchain in Accounting: A Bibliometric Analysis - INDAH SYAFA'ATUL ULA; Totok Dewayanto (Pusat P2M Politeknik Negeri Batam, 2024)
Abstract. Blockchain has emerged as a technology that will change the field of accounting. This technology offers unmatched transparency, security and efficiency in financial transactions and reporting. This research explores the potential of blockchain to revolutionize accounting practices, teaching in improving the accuracy, security and reflection of financial data. Using bibliometric analysis and PRISMA flow charts, this research analyzes trends and developments in blockchain research in the accounting field from 2019 to 2024. This research uses bibliometric analysis tools from R-Packages software and Biblioshiny WebInterface. This analysis is based on data from the Scopus database, identifying publication patterns, collaboration networks, and influential journals. This research uses the Technology-Organization-Environment (TOE) framework to understand the factors that influence the application of blockchain in accounting. By integrating bibliometric methods with the TOE framework, this research offers a detailed examination of blockchain's impact on accounting, as well as highlighting key areas for further research. These findings aim to support accounting professionals in effectively utilizing blockchain technology to improve operational efficiency and prevent fraud, as well as contribute to the wider adoption and integration of blockchain in the accounting field. Keywords: Blockchain, Accounting, Bibliometric Analysis, Scopus, R-Packages, Biblioshiny, Publication Trends, Citations.